Assessment of the supply chain of soursop (Annona muricata L.) fruit and leaves in Ibadan, Nigeria (Agriculture, Food, and Natural Resources Journal, 2024)
This study assessed the supply chain of soursop (Annona muricata L.) fruit and leaves in Ibadan, Oyo State, Nigeria, focusing on economic viability, local demand, and challenges faced by traders. Using a purposive sampling method, three major markets—Oje, Bode, and Ayeye—were selected based on their soursop trading activity, and 45 respondents were chosen through simple random sampling. Data were collected through semi-structured questionnaires, with tables employed as a descriptive tool to analyse results. Findings reveal that soursop trading is predominantly led by middle-aged women between 41 and 50 years old, with either a primary education or no formal education, possessing over 12 years of experience in the trade. Results showed that 73.3% of respondents were married. Soursop is mainly sourced from surrounding villages, with 62.2% of respondents relying on rural suppliers. Additionally, 100% of traders identified the fruit as the most profitable product, and 75.56% of traders were affiliated with trade associations that facilitated rural access and improved bargaining leverage. Key challenges include seasonal shortages and transportation constraints. The study recommends supporting soursop cultivation among individual farmers, along with improved market access and infrastructure enhancements to increase supply stability.
Keywords: Agricultural product; Challenges; Trade; Traditional medicine; Rural; Village